Penggunaan Ikan Hiu sebagai bahan Obat Dalam Perspektif Hukum Islam - Prathita Vidya Wikasitakusuma; Oman Fathurohman sw (An-Najat, 2024)
Sharks in developing their derivative products for pharmaceutical and food purposes, as well as considerations of Islamic law regarding their permissibility for consumption. Indonesia, as a maritime nation rich in marine resources, holds significant potential in managing shark populations. Sharks not only have high economic value through the utilization of various parts such as meat, bones, and skin but also provide valuable raw materials such as liver oil and bone gelatin rich in nutrients. The study notes that these products contain active components like squalene, vitamin A, and omega-3, which offer significant health benefits for treatment and prevention of diseases. Moreover, from an Islamic legal perspective, the majority of scholars regard sharks as halal for consumption, aligning with principles from the Qur'an, Hadith, and the perspectives of Sunni fiqh schools. The importance of implementing the Halal Product Assurance System (SJPH) in the processing of shark products is also discussed to ensure that all produced items meet cleanliness standards and Islamic values. Thus, this research underscores the substantial potential and relevance of sharks in sustainable fisheries development and halal-oriented pharmaceutical industries.